PERAN KEJAKSAAN NEGERI KARAWANG DALAM UPAYA PREVENTIF MENANGGULANGI TINDAK PIDANA KORUPSI DI KABUPATEN KARAWANG - Muhamad Abas; Danang Irwanto; Sartika Dewi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Corruption is a serious issue that has a broad impact on economic stability, social structures, and public trust. Karawang Regency, as a region with rapid economic growth, also faces a high risk of corruption. The Karawang District Prosecutor’s Office holds a strategic role in preventive efforts through various educational and supervisory programs. The research problem or main discussion in this study is how the Karawang District Prosecutor’s Office plays a role in preventing corruption crimes and whether the relationship between the legal structure, legal substance, and legal culture can support efforts to prevent corruption by the prosecutor's office. This research is normative legal research with a juridical-normative approach, encompassing statutory and conceptual approaches. The data used are secondary data obtained through literature studies of legislation, prosecutorial policies, and relevant legal literature. Data analysis is carried out descriptively-analytically using legal interpretation techniques and comparative analysis. The research results show that the Karawang District Prosecutor’s Office has implemented various preventive strategies, such as the "Prosecutors Enter Schools" (Jaksa Masuk Sekolah/JMS) Program, the "Prosecutors Guard Villages" (Jaksa Jaga Desa) Program, and the "Prosecutors as Fishermen's Friends" (Jaksa Sahabat Nelayan) Program. In addition, supervision of regional strategic projects is carried out to prevent abuse of authority. However, there are challenges such as limited human resources, lack of coordination between institutions, and low public legal awareness. By strengthening regulations, transparency, and accountability, it is expected that corrupt practices can be minimized and the integrity of government governance can be enhanced